ТОКОВЫЕ ХАРАКТРИСТИКИ ФОТОЭЛЕКТРИЧЕСКОГО МОДУЛЯ СОЛНЕЧНОЙ ЭНЕРГИИ - Игамкулова, З.М.; Юлдашев, У.Ю. (SCIENCE and SOCIETY, 2023)
This article defines a circuit-based PV cell simulation model to evaluate the cell's electrical behavior in relation to changes in environmental parameters, such as temperature and light. The electrical model of the photovoltaic module is determined based on mathematical equations. The general model was implemented in the MATLAB/Simulink environment and accepts illumination as variables and outputs the VAX.
Keywords: photovoltaics (PV); photocells; Matlab; photovoltaic module; simulation